1977
DOI: 10.1021/i360061a006
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of Hydrogen Sulfide. Influence of Pore Structure and Chemical Composition of Various Porous Substances

Abstract: systems could favor the localization of tellurium either by means of interstitial or substitutional solid solution.The nature of the active sites in oxidative dehydrogenation of 1-butene to butadiene has also been discussed in terms of possible formation of Te==O groups or modification of M-0 groups previously present or even formation of Te==O M e 0 gem groups. AcknowledgmentsWe thank Professor I. Pasquon for encouragement and useful discussion and Italian Consiglio Nazionale delle Ricerche (Rome) for financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 11 publications
1
25
1
1
Order By: Relevance
“…Although the volume of small pores is still available to nitrogen molecules, it is not active in the process of hydrogen sulfide adsorption. This is probably the result of the fouling effect of sulfur or/and sulfuric acid on the catalytic properties of the adsorbents (25,30,31). Similar trends were observed for activated carbons in which even after exhaustion a significant volume of micropores was still available for nitrogen adsorption (14,(21)(22)(23).…”
Section: Figure 1 H2s Breakthrough Curves For Initial Sludge-derivedsupporting
confidence: 57%
“…Although the volume of small pores is still available to nitrogen molecules, it is not active in the process of hydrogen sulfide adsorption. This is probably the result of the fouling effect of sulfur or/and sulfuric acid on the catalytic properties of the adsorbents (25,30,31). Similar trends were observed for activated carbons in which even after exhaustion a significant volume of micropores was still available for nitrogen adsorption (14,(21)(22)(23).…”
Section: Figure 1 H2s Breakthrough Curves For Initial Sludge-derivedsupporting
confidence: 57%
“…Fly ash may also pose high reactivity to the sorbents because of its well developed pore structure and greater specific surface area [10,11]. Steijins and Mars [12] studied the influence of pore structure of different substances on their desulfurization performance and found that micropore less than 0.5-1 nm had the highest catalytic activity. In our previous studies [13,14], iron oxides based sorbent supported on fly ash have shown comparably good performance during hot coal gas desulfurization.…”
Section: Introductionmentioning
confidence: 99%
“…Following the arguments presented above, more sulfur is likely adsorbed in the very small pores of this material, and this process is enhanced by changes in the composition of the solid during heat treatment between 800 and 950 • C. Since elemental sulfur is the predominant product of hydrogen sulfide oxidation on activated carbons (17,25,(28)(29)(30)(31) its presence on SCS-950E can be linked to a relatively high content of a highly carbonized (after treatment at 950…”
Section: Resultsmentioning
confidence: 87%